Alendronate, a double-edged sword acting in the mevalonate pathway. - Tricarico, Paola Maura; Girardelli, Martina; Kleiner, Giulio; Knowles, Alessandra; Valencic, Erica; Crovella, Sergio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Aminobisphosphonate aledronate is a compound commonly used clinically for the treatment of osteoporosis and other bone diseases, as a result of it preventing bone resorption. However, in previous years it has also been used to obtain cellular and animal models of a rare genetic disorder termed Mevalonate Kinase Deficiency (MKD). MKD is caused by mutations affecting the mevalonate kinase enzyme, in the cholesterol pathway and alendronate can be used to biochemically mimic the genetic defect as it inhibits farnesyl pyrophosphate synthase in the same pathway. Despite evidence in favor of the inhibition exerted on the mevalonate pathway, there is at least one clinical case of MKD in which alendronate improved not only skeletal and bone fractures, as expected, but also MKD clinical features. Based on this finding, the present study assessed the anti‑inflammatory properties of this aminobisphosphonate in vitro. No anti‑inflammatory effects of alendronate were observed in the in vitro experiments. Since MKD lacks specific treatments, these results may assist scientists and physicians in making the decision as to the most suitable choice of therapeutic compounds for this neglected disease.